Effects of Self‐Conditioning Techniques (Self‐Hypnosis) in Promoting Weight Loss in Patients with Severe Obesity: A Randomized Controlled Trial. Issue 9 (17th September 2018) - Bo, Simona; Rahimi, Farnaz; Goitre, Ilaria; Properzi, Bice; Ponzo, Valentina; Regaldo, Giuseppe; Boschetti, Stefano; Fadda, Maurizio; Ciccone, Giovannino; Abbate Daga, Giovanni; Mengozzi, Giulio; Evangelista, Andrea; et al.
Abstract: Objective: The usefulness of the rapid‐induction techniques of hypnosis as an adjunctive weight‐loss treatment has not been defined. This randomized controlled trial evaluated whether self‐conditioning techniques (self‐hypnosis) added to lifestyle interventions contributed to weight loss (primary outcome), changes in metabolic and inflammatory variables, and quality of life (QoL) improvement (secondary outcomes) in severe obesity. Methods: Individuals (with BMI = 35‐50 kg/m 2 ) without organic or psychiatric comorbidity were randomly assigned to the intervention ( n  = 60) or control arm ( n  = 60). All received exercise and behavioral recommendations and individualized diets. The intervention consisted of three hypnosis sessions, during which self‐hypnosis was taught to increase self‐control before eating. Diet, exercise, satiety, QoL, anthropometric measurements, and blood variables were collected and measured at enrollment and at 1 year (trial end). Results: A similar weight loss was observed in the intervention (−6.5 kg) and control (−5.6 kg) arms (β = −0.45; 95% CI: −3.78 to 2.88; P  = 0.79). However, habitual hypnosis users lost more weight (−9.6 kg; β = −10.2; 95% CI: −14.2 to −6.18; P  < 0.001) and greatly reduced their caloric intake (−682.5 kcal; β = −643.6; 95% CI: −1064.0 to −223.2; P  = 0.005) in linear regression models. At trial end, the intervention arm showed lower C‐reactive protein values (β = −2.55; 95% CI: −3.80 to −1.31; P  < 0.001), higher satiety (β = 19.2; 95% CI: 7.71‐30.6; P  = 0.001), and better QoL (β = 0.09; 95% CI: 0.02‐0.16; P  = 0.01). Conclusions: Self‐hypnosis was not associated with differences in weight change but was associated with improved satiety, QoL, and inflammation. Indeed, habitual hypnosis users showed a greater weight loss.